Grain Storage, Post-Harvest and IC - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A completely revamped course on Information and Communication (IT skills, presentations) has been added on to NRI s PGDip courses on Grain Storage Management and Post Harvest Horticulture (both from 11 March to 28th June 2002). Students aiming for...